Socioeconomic conditions of elderly people in Kosovo: a cross-sectional study - Jerliu Naim; Toçi Ervin; Burazeri Genc; Ramadani Naser; Brand Helmut (BMC, 2012)
Abstract Background Kosovo is the newest state in Europe facing a particularly difficult socioeconomic and political transition. The available evidence on socioeconomic conditions and quality of life of elderly people in Kosovo is scarce notwithstanding the ageing trend due to lowering of fertility rates and a higher life-expectancy. In this context, the aim of our study was to assess the socioeconomic conditions of elderly people in post-war Kosovo. Methods A cross-sectional study was conducted in Kosovo in January-March 2011 including an age- sex-and residence (urban vs. rural)-stratified sample of 1,890 individuals (83.5% response) aged 65 years and over. A structured questionnaire included assessment of socio-demographic and socioeconomic characteristics including educational level and self-perceived poverty. Binary logistic regression was used to assess the association of self-perceived poverty with socio-demographic and socioeconomic factors. Results The educational level in this representative sample of elderly people in Kosovo was quite low, particularly among women. About 47% of respondents perceived themselves as poor, or extremely poor (41% of men and 52% of women). In multivariable-adjusted models, self-perceived poverty was higher among older women, low educated individuals, urban residents, and elderly individuals living alone. Conclusions Findings from this study indicate that the socioeconomic situation of the elderly population in Kosovo is rather challenging. Demographic trends coupled with the economic and political transition raise serious concerns about increasing needs for socioeconomic support of elderly people in Kosovo. Specific policies and actions should be considered by a number of stakeholders, including government and civil society in transitional Kosovo.